Cerebrospinal fluid diversion versus bariatric surgery in the management of idiopathic intracranial hypertension. (2nd January 2020) - Merola, Joseph; Selezneva, Liudmila; Perkins, Ryan; Lang, Jozsef; Barry, Jonathan; Leach, Paul
Abstract: Background: Idiopathic intracranial hypertension (IIH) is a condition affecting predominantly young women with increased body mass index (BMI). Obesity with the related metabolic and biochemical complications are thought to be involved in the pathogenesis of the condition. The aim of this study is to evaluate the safety, outcomes and economic implications of two treatment options for IIH. Methods: We retrospectively analysed cases of morbidly obese IIH patients treated by cerebrospinal fluid (CSF) shunting procedures between 2006 and 2016 in our department and compared their outcome with that of 69 patients undergoing bariatric surgery between 2015 and 2016. Results: A total of 42 female patients with IIH underwent de-novo shunting procedures during the study period. There was a high rate of shunt revisions (67%) and further weight gain in the majority of patients who had the insertion of CSF shunts. Of the 69 female patients undergoing bariatric surgery 4.3% required interventions related to their surgery with a significantly fewer number of hospital inpatient days. Furthermore, in the patients undergoing bariatric surgery, there was a significant improvement in all obesity-related complications. Conclusions: CSF shunting procedures do not address the aetiological factor of IIH and are associated with high rates of morbidity and further weight gain. Bariatric surgery is not only efficacious in the management of patients with IIH but is associated with significant improvements in other obesity-related comorbidities. Bariatric surgery is safe and more cost-effective than CSF shunting.